A Methionine-Induced Animal Model of Schizophrenia: Face and Predictive Validity - Wang, Lien (Int J Neuropsychopharmacol, 2015)
BACKGROUND: Modulating the methylation process induces broad biochemical changes, some of which may be involved in schizophrenia. Methylation is in particular central to epigenesis, which is also recognized as a factor in the etiology of schizophrenia. Because methionine administration to patients with schizophrenia has been reported to exacerbate their psychotic symptoms and because mice treated with methionine exhibited social deficits and prepulse inhibition impairment, we investigated whether methionine administration could lead to behavioral changes that reflect schizophrenic symptoms in mice. METHODS: l-Methionine was administered to mice twice a day for 7 days. RESULTS: We found that this treatment induces behavioral responses that reflect the 3 types of schizophrenia-like symptoms (positive, negative, or cognitive deficits) as monitored in a battery of behavioral assays (locomotion, stereotypy, social interaction, forced swimming, prepulse inhibition, novel object recognition, and inhibitory avoidance). Moreover, these responses were differentially reversed by typical haloperidol and atypical clozapine antipsychotics in ways that parallel their effects in schizophrenics. CONCLUSION: We thus propose the l-methionine treatment as an animal model recapitulating several symptoms of schizophrenia. We have established the face and predictive validity for this model. Our model relies on an essential natural amino acid and on an intervention that is relatively simple and time effective and may offer an additional tool for assessing novel antipsychotics.